The Impact of Entrepreneurship Education and Entrepreneurial Mindset on Entrepreneurial Intention: The Mediation Role of Digital Literacy - Dias Intan Sholatiah; Sudarmiatin Sudarmiatin; Dwi Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the impact of entrepreneurship education and entrepreneurial mindset on entrepreneurial intention through digital literacy among vocational high school (SMK) students in the Praya Tengah area, Central of Lombok. Using the theory of planned behavior as a theoretical basis, this quantitative study involved 199 students selected through proportional random sampling. Data were collected through questionnaires and analyzed using SEM-PLS 4.0. The results showed that entrepreneurship education and entrepreneurial mindset had a significant effect on entrepreneurial intention, with digital literacy as a mediating variable. These findings indicate that strengthening digital literacy can improve students’ entrepreneurial readiness, thus requiring entrepreneurship education programs that are integrated with digital competencies in vocational students.